Preface: 7th International Conference on Information Science and Electronic Technology (ISET 2025) - Eipstein, Meredith; Mi, Feiqiao (Transactions on Computer Science and Intelligent Systems Research, 2025)
We are pleased to announce that the 2025 7th International Conference on Information Science and Electronic Technology (ISET 2025) was successfully held in Venice, Italy during July 12-13, 2025. The objective of this conference is to provide a platform for researchers, engineers, academicians as well as industrial professionals from all over the world to present their research results and development activities in information science, computer applications, mechatronics, electrical engineering, and electronic technology. This conference provides opportunities for the delegates to exchange new ideas and application experiences face to face, to establish business or research relations, and to find global partners for future collaboration. There were over 40 participants attended ISET 2025. During the conference, the conference model was divided into three sessions, including oral presentations, keynote speeches, and Q&A discussion. Their insightful speeches had triggered heated discussion in the conference. Every participant praised this conference for disseminating useful and insightful knowledge. We would like to acknowledge all of those who have supported ISET 2025. Each individual and institutional help were very important for the success of this conference. Especially we would like to thank the organizing committee for their valuable advices in the organization and helpful peer review of the papers. The Conference Scientific Committee Venice, Italy